Anatomical Variations of Celiac Trunk Branching Pattern in Different Ethnic Groups in Population of Karachi by 3D MDCTA - Rosheena Nabeel Khan, Abdul Rehman, Fauzia Perveen, Muhammad Hussain Siddiqui, Naheed Akhtar, Nuzhat Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate the frequency of branching pattern of celiac trunk variations in different ethnic group in population of Karachi. Study Design: Cross- sectional study Duration: March, 2017- August, 2017. Place: Ziauddin hospital Karachi, Clifton campus, Department of Radiology & Anatomy Method: Total 160 participants were selected with the age range between 20-60 years old male & female adults. The subjects who were recruited in present study were those who came for 3D MDCTA without any upper abdominal vascular or visceral pathologies. Participants were interviewed to collect their demographic particulars and categorize them in different ethnic groups. Variation of Celiac trunk was analysed by Uflacker’s classification. Statistical analysis was completed on SPSS (version 20) and all the data has been presented in percentage and frequency. Results: Classical celiac trunk was found to be the highest in Urdu Speaking i.e. 52 (32.5%) individuals followed by Punjabi speaking 36(22.5%) and 28(17.5%) individuals in Sindhi speaking and least was found in pakhtoon speaking 18(11.25 %) individuals in our study participants. Variant of Celiac trunk was found to be highest in Urdu speaking exhibiting a frequency of 13(8.125 %) individuals. It was followed by Pakhtoon, Sindhi and Punjabi speaking with the frequency of 7(4.375%), 4 (2.5%) and 2(1.25%) individuals respectively. Practical Implication: Present study reports celiac trunk variations in Pakistani population in different ethnic groups. The prevalence of celiac trunk variations in different ethnic groups found in our study was low but these variations may cause catastrophic injuries while doing laproscopic surgeries or Chemoembolization for liver cancer. Vascular anatomical variations of celiac trunk mostly found accidently during interventional or radiological procedures so it should be reported routinely to create awareness regarding vascular variations specifically in different ethnic groups. This data may be utilized by the radiologists and surgeon to reduce catastrophic injuries for patient well being. Conclusion: It has been concluded that vascular anatomical variations of celiac trunk found accidently during interventional or radiological procedures so it is essential to have a knowledge of vascular variations and their presence in different ethnic groups. This data may be utilized by the radiologists and surgeon to avoid injuries specific to Pakistani population. Keywords: Anastomosis, Celiac Trunk, Variations, Multidetector Computer Tomographic Angiography, Laproscopic